PROFIL PERESEPAN PENGGUNAAN ANTIHIPERTENSI PADA PASIEN RAWAT JALAN DI PUSKESMAS SUNGAI ULIN PERIODE OKTOBER 2020 - Normaidah Normaidah; Amalia Risna; Jauhar Latifah; Linda Permata Sari; Ronalisa Ronalisa; Henny Maryani; Difa Intannia (Jurnal Insan Farmasi Indonesia, 2022)
Hypertension is a disease that often causes death because many people do not realize it. People have hypertension if the blood pressure above 140/90 mmHg after regular checking. In Sungai Ulin Public health center, hypertension is the second-highest disease. The study aimed to determine the characteristics of hypertensive patients and the profile of prescribing the use of anti-hypertensive drugs in outpatients in the period October 2020 at Sungai Ulin Public health center. This research is an observational descriptive study using retrospective data with the inclusion criteria. A population of all prescription anti-hypertensive drugs given to outpatients in the period October 2020 in Sungai Ulin Public health center (87 prescriptions). The results showed the percentage of prescription use of anti-hypertensive drugs, namely women who received more anti-hypertensive prescriptions as many as 59 (65,02%) prescriptions, while the age criteria from > 65 years was (26,43%). The majority of drugs were given in Puskesmas Sungai Ulin was amlodipine with a percentage of 72,41%.